Heat-resistant high-hardness engineering plastic and preparation method thereof

By growing an amorphous carbon-silicon-molybdenum film on modified polyimide surfaces, the plastic's mechanical properties and wear resistance are enhanced, addressing the limitations of traditional polyimides in terms of hardness and thermal stability.

CN119242040AInactive Publication Date: 2025-01-03GUANGZHOU ZHONGTUO PLASTIC MOLD CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411158558.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-22
Publication Date
2025-01-03
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Polyimide engineering plastics exhibit low hardness, poor plasticity, and poor wear resistance due to strong molecular interactions, limiting their application in fields requiring high mechanical properties and thermal stability.

Method used

A heat-resistant and high-hardness engineering plastic is prepared by in-situ growing an amorphous carbon-silicon-molybdenum film on the surface of a modified polyimide, achieved through a series of chemical reactions and plasma deposition processes, including the introduction of an indene group into the polyimide molecular chain and a one-step polymerization method.

Benefits of technology

The modified polyimide exhibits improved mechanical properties, reduced thermal expansion coefficient, enhanced wear resistance, and increased surface hardness, thereby addressing the limitations of traditional polyimides.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005005777240000071
    Figure BDA0005005777240000071
  • Figure BDA0005005777240000081
    Figure BDA0005005777240000081
Patent Text Reader

Abstract

The invention discloses heat-resistant high-hardness engineering plastic and a preparation method thereof, and relates to the technical field of engineering materials. The acyl chloride group of 3, 4-dinitrobenzoyl chloride reacts with the amino group of 5-aminomethyl indane, and an indene group with an alicyclic structure is introduced, so that a rigid structure is introduced into a later polyimide molecular chain, the mechanical property of the plastic is improved, an amide structure is generated, the formation of hydrogen bonds is promoted, the thermal expansion coefficient of the plastic is reduced, and the heat resistance is improved; then nitro is reduced through palladium carbon, and modified polyimide is prepared through one-step polymerization with dianhydride; the method comprises the following steps: modifying the polyimide through carbon / silicon / molybdenum mixed plasma current bombardment, forming an amorphous carbon-silicon film on the surface through in-situ growth, obviously improving the surface hardness of the polyimide, and on the basis, doping the molybdenum element to reduce the friction coefficient of the amorphous carbon-silicon film and reduce wear when friction is generated, thereby improving the wear resistance of the plastic and enhancing the mechanical property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of engineering materials, in particular to a heat-resistant high-hardness engineering plastic and a preparation method thereof. Background Art

[0002] Since the middle of the last century, with the rapid development of science and technology, the fields of aerospace, national defense, biomedicine, microelectronics, etc. have put forward higher and higher requirements for material performance, such as good thermal stability, excellent mechanical properties, radiation resistance, and chemical resistance. Among them, polyimide (PI) has excellent mechanical properties because of the rigid imide heterocycle in the molecular chain, and the PI molecular structure is easy to be modified, so it is widely favored by researchers.

[0003] However, since the main chain of polyimide molecules generally contains benzene rings and imide rings, electronic polarization and crystallization result in strong molecular chain interactions between polyimide molecules, causing the molecules to stack tightly. As engineering plastics, they have disadvantages such as low hardness, poor plasticity, poor wear resistance, and high wear rate, which restricts the application of polyimide in more fields. Therefore, it is very important to invent a high-strength, wear-resistant, and high-temperature resistant polyimide plastic. Summary of the invention

[0004] The object of the present invention is to provide a heat-resistant high-hardness engineering plastic and a preparation method thereof, so as to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a heat-resistant and high-hardness engineering plastic, wherein the heat-resistant and high-hardness engineering plastic is prepared by in-situ growing an amorphous carbon-silicon-molybdenum film on the surface of a modified polyimide.

[0006] Furthermore, the modified polyimide is prepared by reacting 3,4-dinitrobenzoyl chloride with 5-aminomethylindane to form a modifier, which is then reduced with palladium carbon and then polymerized with dianhydride in one step.

[0007] Furthermore, the dianhydride is a mixture of one or more of cyclobutanetetracarboxylic dianhydride, 1,2,4,5-cyclohexanetetracarboxylic dianhydride, and pyromellitic dianhydride.

[0008] Furthermore, the in-situ grown amorphous carbon-silicon-molybdenum film is obtained by magnetron sputtering a graphite target, a molybdenum target, and a silicon target, and then introducing the mixed plasma into a vacuum chamber and controlling the current of the mixed plasma to grow on the surface of the modified polyimide.

[0009] Furthermore, a method for preparing heat-resistant and high-hardness engineering plastics comprises the following preparation steps:

[0010] (1) Dissolve 6-10 parts of 5-aminomethylindane and 12-20 parts of triethylamine in 54-88 parts of tetrahydrofuran, cool to 0-10° C., add 4-8 parts of 3,4-dinitrobenzoyl chloride, stir at 600 rpm for 20-40 min, heat to 20-30° C., react for 8-12 h, and then concentrate to obtain a modifier;

[0011] (2) 8 to 14 parts of a modifier, 0.8 to 1.4 parts of palladium carbon, and 64 to 112 parts of anhydrous ethanol are mixed uniformly, the temperature is raised to 70 to 76° C., 2 to 6 parts of hydrazine hydrate are slowly added dropwise, the reaction is carried out for 10 to 16 hours, the filtrate is filtered, 80 to 140 parts of deionized water are added under stirring at 600 rpm, the filter cake is filtered, washed twice with deionized water, and dried at 50 to 60° C. for 8 to 12 hours to obtain a reduction modifier;

[0012] (3) Under a nitrogen atmosphere, 5 to 9 parts of a reducing modifier, 4 to 8 parts of a dianhydride, and 78 to 136 parts of m-cresol are mixed uniformly, stirred at 80 to 90° C. and 800 rpm for 0.5 to 1.5 h, heated to 110 to 130° C., 0.5 to 0.9 parts of isoquinoline are added, and stirring is continued for 0.5 to 1.5 h, and then heated to 190 to 210° C. for reaction for 8 to 10 h, 100 to 180 parts of ethanol are added, and the filter cake is filtered and purified, and then dried at 90 to 100° C. for 12 to 16 h to obtain a modified polyimide;

[0013] (4) Place the modified polyimide in a vacuum of 3.0x10 -3 Pa environment, then, fill with argon gas, clean at 400V bias voltage and 1000V ion beam voltage in turn, each time for 20min, introduce mixed plasma by magnetron sputtering graphite target, molybdenum target and silicon target, and control the carbon, molybdenum and silicon plasma currents, deposit for 3 to 5h under the conditions of argon gas flow rate of 35sccm and bias voltage of -70V, and obtain composite polyimide;

[0014] (5) 74-146 parts of composite polyimide, 5-9 parts of zinc stearate, and 1-3 parts of diethyl phthalate are mixed uniformly, and the mixture is extruded and granulated at a head temperature of 175-185° C., a screw speed of 150-250 r / min, an extrusion pressure of 4-12 MPa, and a shear rate of 100-300 s -1 , obtain heat-resistant and high-hardness engineering plastics.

[0015] Furthermore, the concentration conditions in step (1) are: vacuum degree of -0.08 MPa, and time of 1 to 3 hours.

[0016] Furthermore, the dripping rate in step (2) is 1 mL / min.

[0017] Furthermore, the purification process in step (3) is as follows: dissolving 1 part of the filter cake in 2 parts of dimethylacetamide, adding 10 parts of ethanol, filtering the filter cake, and repeating the process 3 times.

[0018] Furthermore, the flow rate of the argon gas introduced in step (4) is 30 sccm.

[0019] Furthermore, in step (4), the carbon, molybdenum and silicon plasma currents are 3.0A, 0.4A and 0.6A respectively.

[0020] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0021] The present invention bombards CC bonds and CH bonds in modified polyimide by carbon / silicon / molybdenum mixed plasma current to form active chains, which are combined with the mixed plasma. At the same time, the active chains react and crosslink with each other, and the mixed plasmas react and combine with each other. The three reactions form a stable crosslinking structure, which blocks the active chains from continuing to overflow, and then in-situ grows an amorphous carbon silicon film on the surface of the modified polyimide, significantly improving the surface hardness of the polyimide. On this basis, the doping of molybdenum elements can reduce the friction coefficient of the amorphous carbon silicon film, reduce wear when friction occurs, and then improve the wear resistance of the plastic and enhance the mechanical properties.

[0022] Among them, the modified polyimide utilizes the reaction of the acyl chloride group of 3,4-dinitrobenzoyl chloride with the amino group of 5-aminomethylindane to introduce the indene group of the alicyclic structure, thereby introducing a rigid structure into the later polyimide molecular chain, thereby improving the mechanical properties of the plastic. At the same time, the amide structure generated by the reaction promotes the formation of hydrogen bonds and inhibits the free movement of the chain segments when the temperature rises, thereby reducing the thermal expansion coefficient of the plastic and improving the heat resistance. Then, the nitro group is reduced to an amino group through palladium carbon to make it carry a diamine, and then it is polymerized with dianhydride through a one-step method to obtain the modified polyimide, thereby improving production efficiency. DETAILED DESCRIPTION

[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the heat-resistant high-hardness engineering plastics prepared in the following examples are as follows:

[0025] Tensile strength: The plastics of the embodiments and comparative examples were made into 0.3 mm films for tensile strength testing, and the testing was performed in accordance with GB / T13022.

[0026] Flexibility: Take the plastics of the embodiments and comparative examples to make a 1 mm plastic sheet, put the plastic sheet tightly on a fixed shaft rod, and then bend it around the shaft rod to observe whether the plastic sheet breaks, and record the minimum diameter of the shaft rod without defects.

[0027] Heat-resistant temperature: Take the plastics of the embodiment and comparative example to make a 5x5cm plastic block, put it into a DRZ-12 high-temperature furnace, keep it warm for one hour after reaching the set temperature, observe whether the plastic melts and deforms, and record the lowest temperature without deformation.

[0028] Abrasion test: Take the same weight of the embodiment and the comparative example, and test the wear resistance of the plastics according to GB / T3960, and record the wear quality.

[0029] Example 1

[0030] (1) Dissolve 6 parts of 5-aminomethylindane and 12 parts of triethylamine in 54 parts of tetrahydrofuran, cool to 0°C, add 4 parts of 3,4-dinitrobenzoyl chloride, stir at 600 rpm for 20 min, heat to 20°C, react for 8 h, and then concentrate at a vacuum degree of -0.08 MPa for 1 h to obtain a modifier;

[0031] (2) 8 parts of the modifier, 0.8 parts of palladium carbon, and 64 parts of anhydrous ethanol were mixed evenly, the temperature was raised to 70°C, 2 parts of hydrazine hydrate were slowly added dropwise at 1 mL / min, the reaction was continued for 10 h, the filtrate was filtered, 80 parts of deionized water were added under stirring at 600 rpm, the filter cake was filtered, washed twice with deionized water, and dried at 50°C for 8 h to obtain a reduction modifier;

[0032] (3) Under a nitrogen atmosphere, 5 parts of a reducing modifier, 4 parts of cyclobutanetetracarboxylic dianhydride, and 78 parts of m-cresol were mixed evenly, stirred at 80° C. and 800 rpm for 0.5 h, then heated to 110° C., 0.5 parts of isoquinoline were added and stirred for 0.5 h, then heated to 190° C. for reaction for 8 h, 100 parts of ethanol were added, the filter cake was filtered out, and purified, 1 part of the filter cake was dissolved in 2 parts of dimethylacetamide, 10 parts of ethanol were added, the filter cake was filtered out, and the process was repeated 3 times, and the mixture was dried at 90° C. for 12 h to obtain a modified polyimide;

[0033] (4) Place the modified polyimide in a vacuum of 3.0x10 -3 Pa environment, argon was filled at a constant flow rate of 30 sccm, and cleaning was carried out successively at a bias voltage of 400 V and an ion beam voltage of 1000 V, each time for 20 min, and mixed plasma was introduced by magnetron sputtering of graphite target, molybdenum target, and silicon target, and deposited for 3 h at an argon flow rate of 35 sccm and a bias voltage of -70 V with a carbon plasma current of 3.0 A, a molybdenum plasma current of 0.4 A, and a silicon plasma current of 0.6 A, respectively, to obtain a composite polyimide;

[0034] (5) 74 parts of composite polyimide, 5 parts of zinc stearate and 1 part of diethyl phthalate were mixed evenly, and extruded into granules after mixing. The head temperature was 175°C, the screw speed was 150 r / min, the extrusion pressure was 4 MPa, and the shear rate was 100 s -1 , obtain heat-resistant and high-hardness engineering plastics.

[0035] Example 2

[0036] (1) 8 parts of 5-aminomethylindane and 16 parts of triethylamine were dissolved in 71 parts of tetrahydrofuran, cooled to 5°C, 6 parts of 3,4-dinitrobenzoyl chloride were added, stirred at 600 rpm for 30 min, heated to 25°C, reacted for 10 h, and concentrated at a vacuum degree of -0.08 MPa for 2 h to obtain a modifier;

[0037] (2) 11 parts of a modifier, 1.1 parts of palladium carbon, and 88 parts of anhydrous ethanol were mixed evenly, the temperature was raised to 73°C, 4 parts of hydrazine hydrate were slowly added dropwise at 1 mL / min, the reaction was continued for 13 h, the filtrate was filtered, 110 parts of deionized water were added under stirring at 600 rpm, the filter cake was filtered, washed twice with deionized water, and dried at 55°C for 10 h to obtain a reduction modifier;

[0038] (3) Under a nitrogen atmosphere, 7 parts of a reducing modifier, 6 parts of 1,2,4,5-cyclohexanetetracarboxylic acid dianhydride, and 107 parts of m-cresol were mixed uniformly, stirred at 85°C and 800 rpm for 1.0 h, then heated to 120°C, 0.7 parts of isoquinoline were added, and stirring was continued for 1.0 h, and then heated to 200°C for reaction for 9 h, 140 parts of ethanol were added, and the filter cake was filtered and purified, 1 part of the filter cake was dissolved in 2 parts of dimethylacetamide, 10 parts of ethanol were added, and the filter cake was filtered, and the process was repeated 3 times, and dried at 95°C for 14 h to obtain a modified polyimide;

[0039] (4) Place the modified polyimide in a vacuum of 3.0x10 -3 Pa environment, argon gas was filled at a constant flow rate of 30sccm, and cleaning was carried out successively at a bias voltage of 400V and an ion beam voltage of 1000V, each time for 20min, and mixed plasma was introduced by magnetron sputtering of graphite target, molybdenum target and silicon target, and the current of carbon plasma was controlled to be 3.0A, the current of molybdenum plasma was controlled to be 0.4A, and the current of silicon plasma was controlled to be 0.6A, and deposition was carried out for 4h under the conditions of argon gas flow rate of 35sccm and bias voltage of -70V to obtain composite polyimide;

[0040] (5) 110 parts of composite polyimide, 7 parts of zinc stearate, and 2 parts of diethyl phthalate were mixed evenly, and then extruded and granulated at a head temperature of 180°C, a screw speed of 200 r / min, an extrusion pressure of 8 MPa, and a shear rate of 200 s -1, obtain heat-resistant and high-hardness engineering plastics.

[0041] Example 3

[0042] (1) Dissolve 10 parts of 5-aminomethylindane and 20 parts of triethylamine in 88 parts of tetrahydrofuran, cool to 10° C., add 8 parts of 3,4-dinitrobenzoyl chloride, stir at 600 rpm for 40 min, heat to 30° C., react for 12 h, and concentrate at a vacuum degree of -0.08 MPa for 3 h to obtain a modifier;

[0043] (2) 14 parts of a modifier, 1.4 parts of palladium carbon, and 112 parts of anhydrous ethanol were mixed evenly, heated to 76°C, 6 parts of hydrazine hydrate were slowly added dropwise at 1 mL / min, reacted for 16 hours, the filtrate was filtered, 140 parts of deionized water were added under stirring at 600 rpm, the filter cake was filtered, washed twice with 28 parts of deionized water, and dried at 60°C for 12 hours to obtain a reduction modifier;

[0044] (3) Under a nitrogen atmosphere, 9 parts of a reducing modifier, 8 parts of pyromellitic anhydride, and 136 parts of m-cresol were mixed evenly, stirred at 90° C. and 800 rpm for 1.5 h, then heated to 130° C., 0.9 parts of isoquinoline were added and stirred for 1.5 h, then heated to 210° C. for reaction for 10 h, 180 parts of ethanol were added, the filter cake was filtered out, and purified, 1 part of the filter cake was dissolved in 2 parts of dimethylacetamide, 10 parts of ethanol were added, the filter cake was filtered out, and the process was repeated 3 times, and the mixture was dried at 100° C. for 16 h to obtain a modified polyimide;

[0045] (4) placing the modified polyimide in an environment with a vacuum degree of 3.0x10-3Pa, filling it with argon at a constant flow rate of 30sccm, cleaning it successively at a bias voltage of 400V and an ion beam voltage of 1000V for 20min each time, introducing a mixed plasma by magnetron sputtering a graphite target, a molybdenum target, and a silicon target, and depositing it for 5h at an argon flow rate of 35sccm and a bias voltage of -70V with a carbon plasma current of 3.0A, a molybdenum plasma current of 0.4A, and a silicon plasma current of 0.6A, respectively, to obtain a composite polyimide;

[0046] (5) 146 parts of composite polyimide, 9 parts of zinc stearate, and 3 parts of diethyl phthalate were mixed uniformly, and extruded into granules after mixing. The head temperature was 185°C, the screw speed was 250 r / min, the extrusion pressure was 12 MPa, and the shear rate was 300 s -1 , obtain heat-resistant and high-hardness engineering plastics.

[0047] Comparative Example 1

[0048] The difference between Comparative Example 1 and Example 2 is that there is no step (1), and step (2) is changed to: 11 parts of 3,4-dinitrobenzoyl chloride, 1.1 parts of palladium carbon, and 88 parts of anhydrous ethanol are mixed evenly, heated to 73°C, 4 parts of hydrazine hydrate are slowly added dropwise at 1 mL / min, reacted for 13 hours, filtered to obtain the filtrate, 110 parts of deionized water are added under stirring at 600 rpm, the filter cake is filtered to obtain, washed twice with 22 parts of deionized water, and dried at 55°C for 10 hours to obtain a reduction modifier. The remaining steps are the same as those in Example 2.

[0049] Comparative Example 2

[0050] The difference between Comparative Example 2 and Example 2 is that there is no step (1), and step (2) is changed to: 11 parts of 5-aminomethylindane, 1.1 parts of palladium carbon, and 88 parts of anhydrous ethanol are mixed uniformly, heated to 73°C, 4 parts of hydrazine hydrate are slowly added dropwise at 1 mL / min, reacted for 13 hours, filtered to obtain the filtrate, 110 parts of deionized water are added under stirring at 600 rpm, the filter cake is filtered to obtain, washed twice with 22 parts of deionized water, and dried at 55°C for 10 hours to obtain a reduction modifier. The remaining steps are the same as those in Example 2.

[0051] Comparative Example 3

[0052] The difference between Comparative Example 3 and Example 2 is that step (3) is different. Step (3) is changed to: Under a nitrogen atmosphere, 7 parts of a reducing modifier, 6 parts of 1,2,4,5-cyclohexanetetracarboxylic acid dianhydride, and 107 parts of m-cresol are mixed evenly, stirred at 25°C and 800 rpm for 24 hours, 0.7 parts of isoquinoline are added, and stirring is continued for 5.0 hours, 0.7 parts of acetic anhydride are added, the temperature is raised to 200°C and the reaction is carried out for 9 hours, 140 parts of ethanol are added, the filter cake is filtered, and purification treatment is performed, 1 part of the filter cake is dissolved in 2 parts of dimethylacetamide, 10 parts of ethanol are added, the filter cake is filtered, and the process is repeated 3 times, and the filter cake is dried at 95°C for 14 hours to obtain a modified polyimide. The remaining steps are the same as those of Example 2.

[0053] Comparative Example 4

[0054] The difference between Comparative Example 4 and Example 2 is that step (4) is different, and step (4) is changed to: the modified polyimide is placed in an environment with a vacuum degree of 3.0x10-3Pa, argon is filled at a constant flow rate of 30sccm, and cleaning is carried out successively at a bias voltage of 400V and an ion beam voltage of 1000V, each time for 20min, and mixed plasma is introduced by magnetron sputtering of molybdenum target and silicon target, and deposited for 4h at a molybdenum plasma current of 0.4A and a silicon plasma current of 0.6A, respectively, under the conditions of an argon flow rate of 35sccm and a bias voltage of -70V, to obtain a heat-resistant and high-hardness engineering plastic. The remaining steps are the same as those in Example 2.

[0055] Comparative Example 5

[0056] The difference between Comparative Example 5 and Example 2 is that step (4) is different. Step (4) is changed to: the modified polyimide is placed in an environment with a vacuum degree of 3.0x10-3Pa, argon is filled at a constant flow rate of 30sccm, and cleaning is carried out successively at a bias voltage of 400V and an ion beam voltage of 1000V, each time for 20min, and mixed plasma is introduced by magnetron sputtering graphite target and silicon target, and deposited for 4h at a carbon plasma current of 3.0A and a silicon plasma current of 0.6A, respectively, under the conditions of an argon flow rate of 35sccm and a bias voltage of -70V, to obtain a heat-resistant and high-hardness engineering plastic. The remaining steps are the same as those in Example 2.

[0057] Comparative Example 6

[0058] The difference between Comparative Example 6 and Example 2 is that step (4) is different. Step (4) is changed to: the modified polyimide is placed in an environment with a vacuum degree of 3.0x10-3Pa, argon is filled at a constant flow rate of 30sccm, and cleaning is carried out successively at a bias voltage of 400V and an ion beam voltage of 1000V, each time for 20min, and mixed plasma is introduced by magnetron sputtering graphite target and molybdenum target, and deposited for 4h at a carbon plasma current of 3.0A and a molybdenum plasma current of 0.4A, respectively, under the conditions of an argon flow rate of 35sccm and a bias voltage of -70V, to obtain a heat-resistant and high-hardness engineering plastic. The remaining steps are the same as those in Example 2.

[0059] Comparative Example 7

[0060] The difference between Comparative Example 7 and Example 2 is that step (4) is different, and step (4) is changed to: 18 parts of modified polyimide, 2 parts of silicon dioxide, 1 part of graphite, and 1 part of molybdenum dioxide are mixed uniformly, and placed in a 185° C. internal mixer for 15 minutes to obtain a heat-resistant high-hardness engineering plastic. The remaining steps are the same as in Example 2.

[0061] Effect example

[0062] Table 1 below shows the performance analysis results of the heat-resistant and high-hardness engineering plastics of Examples 1 to 3 and Comparative Examples 1 to 7 of the present invention.

[0063] Table 1

[0064]

[0065]

[0066] From the comparison of the experimental data of Examples 1, 2, and 3 with those of Comparative Example 1, it can be found that by introducing the indene group of the alicyclic structure through 5-aminomethylindane, a rigid structure can be introduced into the polyimide molecular chain in the later stage, thereby improving the mechanical properties of the plastic; from the comparison of the experimental data of Examples 1, 2, and 3 with those of Comparative Example 2, it can be found that the amide structure generated by the acyl chloride group of 3,4-dinitrobenzoyl chloride participating in the reaction can promote the formation of hydrogen bonds, inhibit the free movement of the chain segments when the temperature rises, thereby reducing the thermal expansion coefficient of the plastic and improving the heat resistance; from the comparison of the experimental data of Examples 1, 2, and 3 with those of Comparative Example 3, it can be found that the modified polyimide prepared by two-step polymerization is not only complex in process, high in cost, and low in efficiency, but also the polyamic acid solution formed in the first step is unstable and easily absorbs water vapor and decomposes, while the polyimide prepared by the one-step polycondensation method has good performance and is also more stable; from the comparison of the experimental data of Examples 1, 2, and 3 with those of Comparative Example 4, it can be found that the addition of amorphous carbon film can The wear of plastics during use is reduced, the surface hardness is improved, and the mechanical properties are enhanced; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 5, it can be found that the formation of amorphous silicon significantly enhances the wear resistance of plastics and improves the heat resistance temperature; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 6, it can be found that the doping of molybdenum elements can reduce the friction coefficient of the amorphous film, reduce wear when friction occurs, and thus improve the wear resistance of the plastic and enhance the mechanical properties; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 7, it can be found that the CC bonds and CH bonds in the modified polyimide are bombarded with mixed plasma current to form active chains, which are combined with the mixed plasma, and at the same time, the active chains react and crosslink with each other, and the mixed plasmas react and combine with each other. The three reactions form a stable crosslinking structure, which prevents the active chains from continuing to overflow, and then in situ grows on the surface of the modified polyimide to form an amorphous carbon silicon film, which can significantly improve the mechanical properties of the polyimide.

[0067] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A heat-resistant and high-hardness engineering plastic, characterized in that: The heat-resistant high-hardness engineering plastic is prepared by in-situ growing an amorphous carbon-silicon-molybdenum film on the surface of modified polyimide.

2. The heat-resistant and high-hardness engineering plastic according to claim 1, characterized in that: The modified polyimide is prepared by reacting 3,4-dinitrobenzoyl chloride with 5-aminomethylindane to form a modifier, which is then reduced with palladium carbon and then polymerized with dianhydride in one step.

3. The heat-resistant and high-hardness engineering plastic according to claim 2, characterized in that: The dianhydride is a mixture of one or more of cyclobutanetetracarboxylic dianhydride, 1,2,4,5-cyclohexanetetracarboxylic dianhydride and pyromellitic dianhydride.

4. The heat-resistant and high-hardness engineering plastic according to claim 1, characterized in that: The in-situ grown amorphous carbon-silicon-molybdenum film is prepared by magnetron sputtering a graphite target, a molybdenum target and a silicon target, and the introduced mixed plasma is combined and grown on the modified polyimide.

5. A method for preparing heat-resistant and high-hardness engineering plastics, characterized in that: The method comprises the following preparation steps: (1) Dissolve 6-10 parts of 5-aminomethylindane and 12-20 parts of triethylamine in 54-88 parts of tetrahydrofuran, cool to 0-10° C., add 4-8 parts of 3,4-dinitrobenzoyl chloride, stir at 600 rpm for 20-40 min, heat to 20-30° C., react for 8-12 h, and then concentrate to obtain a modifier; (2) 8 to 14 parts of a modifier, 0.8 to 1.4 parts of palladium carbon, and 64 to 112 parts of anhydrous ethanol are mixed uniformly, the temperature is raised to 70 to 76° C., 2 to 6 parts of hydrazine hydrate are slowly added dropwise, the reaction is carried out for 10 to 16 hours, the filtrate is filtered, 80 to 140 parts of deionized water are added under stirring at 600 rpm, the filter cake is filtered, washed twice with deionized water, and dried at 50 to 60° C. for 8 to 12 hours to obtain a reduction modifier; (3) Under a nitrogen atmosphere, 5 to 9 parts of a reducing modifier, 4 to 8 parts of a dianhydride, and 78 to 136 parts of m-cresol are mixed uniformly, stirred at 80 to 90° C. and 800 rpm for 0.5 to 1.5 h, heated to 110 to 130° C., 0.5 to 0.9 parts of isoquinoline are added, and stirring is continued for 0.5 to 1.5 h, and then heated to 190 to 210° C. for reaction for 8 to 10 h, 100 to 180 parts of ethanol are added, and the filter cake is filtered and purified, and then dried at 90 to 100° C. for 12 to 16 h to obtain a modified polyimide; (4) Place the modified polyimide in a vacuum of 3.0x10 -3 Pa environment, then, fill with argon gas, clean at 400V bias voltage and 1000V ion beam voltage in turn, each time for 20min, introduce mixed plasma by magnetron sputtering graphite target, molybdenum target and silicon target, and control the carbon, molybdenum and silicon plasma currents, deposit for 3 to 5h under the conditions of argon gas flow rate of 35sccm and bias voltage of -70V, and obtain composite polyimide; (5) 74-146 parts of composite polyimide, 5-9 parts of zinc stearate, and 1-3 parts of diethyl phthalate are mixed uniformly, and the mixture is extruded and granulated at a head temperature of 175-185° C., a screw speed of 150-250 r / min, an extrusion pressure of 4-12 MPa, and a shear rate of 100-300 s -1 , obtain heat-resistant and high-hardness engineering plastics.

6. The method for preparing a heat-resistant and high-hardness engineering plastic according to claim 5, characterized in that: The concentration conditions of step (1) are: at a vacuum degree of -0.08 MPa and a time of 1 to 3 hours.

7. The method for preparing a heat-resistant and high-hardness engineering plastic according to claim 5, characterized in that: The rate of the dropping in step (2) is 1 mL / min.

8. The method for preparing a heat-resistant and high-hardness engineering plastic according to claim 5, characterized in that: The purification process of step (3) is as follows: dissolve 1 part of the filter cake in 2 parts of dimethylacetamide, add 10 parts of ethanol, filter and take the filter cake, and repeat 3 times.

9. The method for preparing a heat-resistant and high-hardness engineering plastic according to claim 5, characterized in that: The flow rate of the argon gas in step (4) is: 30 sccm.

10. The method for preparing a heat-resistant and high-hardness engineering plastic according to claim 5, characterized in that: The carbon, molybdenum and silicon plasma currents in step (4) are 3.0A, 0.4A and 0.6A respectively.

Citation Information

Patent Citations

  • Polyimide film and preparation methods thereof

    CN104151823A

  • Application of carbon-rich amorphous thin film in high-voltage resistant insulating material

    CN105529118A

  • Acrylonitrile copolymer adhesive and application thereof in lithium ion batteries

    CN106220779A

  • Polyimide compound and molded article containing said polyimide compound

    CN111770951A

  • Acrylonitrile copolymer adhesive applied to lithium ion battery

    CN117701199A